Cybernetic Thinking: Serialist and Wholist style as an English Grammar Problem Solving Learning Perspective during the Pandemic - Susanto, Ferri; Khan, Ali; Deng, Changjiang; Cardinal, Kaufmann (Al-Hijr: Journal of Adulearn World, 2022)
This study aims to describe how students think cybernetics in solving English grammar problems using serialist and wholist thinking styles. The qualitative approach used in this study is because it is more descriptive. Data collection techniques used questionnaires and instruments in the form of written tests in solving English Grammar questions and combined with interviews. This research was conducted at the Faculty of English Tarbiyah in the second semester of Fatmawati Sukarno State Islamic University Bengkulu in the 2020/202 academic year. Purposive sampling technique was used to take research samples. The sample of this study consisted of two students who had the serialist thinking style and two students who had the wholist thinking style. The results showed that information in the form of questions received by students who had serialist and wholist thinking styles entered the five senses directly through the senses of sight and hearing. The attention process occurs after the question is read and understood so that perception arises. The perceptions that arise are taken as necessary concepts from long-term memory to solve problems. During the retrieval, students who have the serialist thinking style are very at risk of improvisation. Meanwhile, for students who have the wholist thinking style, the concepts needed in short term memory are not stored properly by long term memory, so these students often experience mistakes and forget when doing retrieval, as a result these students are more likely to generalize excessively. These two thinking styles are expected to be able to become perspectives on the development of thinking styles in the teaching and learning process during the current pandemic.